Oil- prone Carboniferous coals (Tettegras Fm.) from the Finnmark Platform : Implications for an alternative and new Petroleum System based on oil generative coals of the Billefjord Gr. in the Barents Region - Moi, Ronny (2008)
In this thesis the aim was to investigate the largely unknown potential of coals of the Tettegras Fm. (Billefjord Gr.) in two wells from the Finnmark Platform and to evaluate the generation and expulsion properties of these coals and to see if evidences suggest that two drill stem test (DST) oils in one of these wells could possibly have some contribution of oil from coals of the Tettegras Fm.